HIV Testing and Counselling in Colombia: Local Experience on Two Different Recruitment Strategies to Better Reach Low Socioeconomic Status Communities - Jaime Galindo-Quintero; Hector Fabio Mueses-Marin; David Montaño-Agudelo; María Virginia Pinzón-Fernández; Inés Constanza Tello-Bolívar; Beatriz Eugenia Alvarado-Llano; Jorge Luis Martinez-Cajas (AIDS Research and Treatment)
HIV testing rates remain very low in Colombia, with only 20% of individuals at risk ever tested. In order to tackle this issue, the Corporacion de Lucha Contra el Sida (CLS) has implemented a multidisciplinary, provider-initiated, population-based HIV testing/counselling strategy named BAFI. In this report, we describe the experience of CLS at reaching populations from low socioeconomic backgrounds in 2008-2009. Two different approaches were used: one led by CLS and local health care providers (BAFI-1) and the other by CLS and community leaders (BAFI-2). Both approaches included the following: consented HIV screening test, a demographic questionnaire, self-reported HIV knowledge and behaviour questionnaires, pre- and posttest counselling, confirmatory HIV tests, clinical follow-up, access to comprehensive care and antiretroviral treatment. A total of 2085 individuals were enrolled in BAFI-1 and 363 in BAFI-2. The effectiveness indicators for BAFI-1 and BAFI-2, respectively, were HIV positive-confirmed prevalence = 0.29% and 3.86%, return rate for confirmatory results = 62.5% and 93.7%, return rate for comprehensive care = 83.3% and 92.8%, and ART initiation rate = 20% and 76.9%. Although more people were reached with BAFI-1, the community-led BAFI-2 was more effective at reaching individuals with a higher prevalence of behavioural risk factors for HIV infection.